Technology Assisted Therapy Innovation for War Trauma: An Intervention Synthesis - Nurzahara Sihombing; M. Agung Rahmadi; Laila Zahra; Putri Ramadhani; Ferius Lahagu; Helsa Nasution; Luthfiah Mawar; Siti Padila; Annisa Ardianti Br Tarigan (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
This meta-synthesis examines in depth the effectiveness of technology-assisted therapy (TAT) in the treatment of war-related trauma through a systematic analysis of 47 empirical studies with a total of 6,842 participants published between 2010 and 2024. The quantitative synthesis indicates that the implementation of TAT demonstrates statistically significant effectiveness in reducing the severity of post-traumatic stress disorder symptoms (d=0.78, 95% CI [0.65, 0.91]), anxiety (d=0.69, 95% CI [0.54, 0.84]), and depression (d=0.72, 95% CI [0.58, 0.86]) among populations affected by armed conflict. Among the various digital modalities, Virtual Reality Exposure Therapy (VRET) exhibits the strongest therapeutic effect (d=0.85) compared with mobile-based intervention (d=0.71) and teletherapy (d=0.68). Further moderator analysis identifies the optimal intervention duration as 12 to 16 weeks, with a significant effect contribution (β=0.34, p<.001) and a relatively moderate dropout rate of 18.7%. These findings extend Tng et al. (2024) by confirming the superiority of VRET and by confirming the significance of therapist support for the effectiveness of TAT (Wu et al., 2025). In contrast to the meta-analysis by Eshuis et al. (2021), which emphasized a single approach, this study reveals that hybrid interventions that integrate multiple digital platforms simultaneously (d=0.89) are superior to single-platform interventions (d=0.67). Overall, the results of this meta-synthesis provide a strong empirical foundation for the development of more comprehensive, adaptive, and contextually relevant TAT protocols for war-related trauma.